2021
DOI: 10.3389/fcell.2021.643942
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers of MicroRNA Signature in Non-small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide and non-small cell lung cancer (NSCLC) accounts for more than 80% of all lung cancer cases. Recent advancements in diagnostic tools, surgical treatments, chemotherapies, and molecular targeted therapies that improved the therapeutic efficacy in NSCLC. However, the 5-years relative survival rate of NSCLC is only about 20% due to the inadequate screening methods and late onset of clinical symptoms. Dysregulation of microRNAs (miRNAs) was frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 123 publications
0
41
0
Order By: Relevance
“…They act as gene regulator by binding to mRNAs and inhibiting their functions (205). Plenty of studies revealed that miRNAs play significant roles, including both oncogenes and tumor suppressors, during the progression and metastasis of lung cancer (206)(207)(208).…”
Section: Microrna (Mirna)mentioning
confidence: 99%
See 1 more Smart Citation
“…They act as gene regulator by binding to mRNAs and inhibiting their functions (205). Plenty of studies revealed that miRNAs play significant roles, including both oncogenes and tumor suppressors, during the progression and metastasis of lung cancer (206)(207)(208).…”
Section: Microrna (Mirna)mentioning
confidence: 99%
“…They act as gene regulator by binding to mRNAs and inhibiting their functions ( 205 ). Plenty of studies revealed that miRNAs play significant roles, including both oncogenes and tumor suppressors, during the progression and metastasis of lung cancer ( 206 208 ). Overexpression of the let-7 family, miR-486, miR-218, miR-34, and miR-200 were proved to inhibit the tumor cell proliferation, invasion and colony formation, though there is no specific article describing their relations with tumor cells bone migration ( 209 212 ).…”
Section: Other Potential Biomarkersmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is a lethal cancer that causes over 1 million deaths a year (Torre et al, 2015;Yan et al, 2020;Zhu et al, 2021). Recently, the rising incidence of lung adenocarcinoma (LUAD), a major type of NSCLC, has become such a concerning issue that tends to surpass lung squamous carcinoma (Tong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In non‐small cell lung cancer (NSCLC), miR‐21 is upregulated in cancer tissue and therefore had been considered as a promising diagnostic and therapeutic marker in NSCLC. 8 However, emerging studies revealed that many miRNAs exhibit dual roles in different cellular contexts. 9 , 10 Specially in cancer, some miRNAs are reported to exert contrary oncogenic or tumor‐suppressive functions, relying on whether their targets are potential tumor suppressors or oncogenes.…”
Section: Introductionmentioning
confidence: 99%